2006
DOI: 10.2113/gsmicropal.52.4.343
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and persistence of foraminifera in introduced mangroves on Moorea, French Polynesia

Abstract: Foraminifera inhabiting the muddy substrata within the coastal mangrove forests (Rhizophora stylosa Griff.) on Moorea, French Polynesia, are distinct from other near shore foraminiferal assemblages around the island. Yet the mangroves were introduced from New Caledonia only in 1937 at Vaianahe Bay; they have since spread to many other sites around Moorea. They invade and occupy mud substrata below Paspalum marshes, the marshes themselves and mud under overhanging Hibiscus stands. The mangrove foraminifera clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Potential consequences and effects of the transfer of benthic foraminifera are virtually unexplored (Langer and Lipps 2006). Studies from the eastern Mediterranean have documented that invasive taxa of benthic foraminifera may become so abundant, that they locally modify the production of calcium carbonate and influence indigenous foraminiferal assemblages (Hyams et al 2002;Langer 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Potential consequences and effects of the transfer of benthic foraminifera are virtually unexplored (Langer and Lipps 2006). Studies from the eastern Mediterranean have documented that invasive taxa of benthic foraminifera may become so abundant, that they locally modify the production of calcium carbonate and influence indigenous foraminiferal assemblages (Hyams et al 2002;Langer 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Murray 1991;Sen Gupta 1999;Culver and Horton 2005). Langer and Lipps (2006) investigated the impact of introduced intertidal vegetation (mangroves recently introduced to Moorea, French Polynesia) on the native foraminiferal fauna and found that the newly created habitat around the roots was colonised by a mixed assemblage of native species from the adjacent lower tidal mud flats and higher tidal salt meadow. We are unaware of any previous published studies on ostracod or foraminiferal faunas in Asian date mussel beds, or any on the impacts of introduced Asian date mussels or cordgrass on these microfaunas.…”
Section: Previous Microfaunal Studiesmentioning
confidence: 99%
“…A few propagules were introduced to one bay, but mangroves are now established around Moorea and on some nearby islands. These mangroves have replaced salt grass (Paspalum vaginatum) marshes and colonized mud flats, leading to efforts to control their spread (Langer and Lipps 2006).…”
Section: Introductionmentioning
confidence: 99%